NAGA MIRCHA (BHUT JOLOKIA) LEPA AS SHOOLAPRASHAMANA (PAIN RELIEVER) IN SANDHIGATAVATA –A CASE STUDY - *Imlikumba,; Pekyom Ringu, (International Journal of Ayurveda and Pharma Research, 2019)
A 45 year old female patient complaining of pain, Sparsha Asahatwa (tenderness), Shotha (inflammation) crackle sounds of the joints and warmth for 4 years but severe since 5 months and restricted movement of bilateral knee join, was being diagnosed as a case of Janu Sandhigata Vata (Osteoarthritis of knee joint) treatment planned with Hingwashtaka Choorna, Maha Yograj Guggulu, Maha Rasnadi Kadha, Gandharva Haritaki Choorna ausadhi and Bahiparimarjana Chikitsa i.e., Naga Mircha Lepa. There was a significant improvement in the scale of pain, range of movement and standing time along with diminution of inflammation and tenderness after treatment. Patient responded to the Ayurvedic treatment. After the therapy patient felt improvement.